Creative imagination and creativity - Di Gregori, Cristina (2018)
In the last decades the idea of creativity has gained increasing interest in the field of philosophy, cognitive sciences, sociology, etc. and there have been renewed contributions regarding the classic idea of creativity. We consider that the contribution of classic pragmatism deserves special mention-particularly in the works of Charles S. Peirce and John Dewey. In this article, we are going to refer exclusively to the Deweyan treatment of this idea. We will expose some consequences of his position-as we interpret it. In effect, we are going to sustain the Dewey moves away from classic demands according to which a creative product involves, neccessarily, a radical transformation of human life, according to the idea of degrees of creativiy; that this Deweyan theory constitutes an interesnting insight for promoting the creative attitude; that the creative process retains the same structure in all cases-science and art, for example-and that creativity is now an intrinsic potentiality of human beings-which may be realiized or not. Finally, we consider the relevance of some Deweyan theses for nowadays positions, as in the case of the cognitive psychologist Robert Weisberg, emphasizing, their coincidences and disagreements.
Nas últimas décadas, a ideia de criatividade tem obtido um aumento de interesse nos campos da filosofia, ciências cognitivas, sociologia, etc. e tem havido uma contribuição renovada com relação à ideia clássica de criatividade. Consideramos que a contribuição do pragmatismo clássico merece uma menção especial - em especial, as obras de Charles S. Peirce e John Dewey. Neste artigo, iremos nos referir, exclusivamente, ao tratamento deweyiano a essa ideia. Sustentaremos que a teoria de Dewey fornece elementos interpretativos que são inovadores e disruptivos com relação à tradição filosófica, inclusive, uma nova concepção de imaginação criativa. Exporemos algumas consequências de sua posição - como nós a interpretamos. Com efeito, sustentaremos que Dewey afasta-se das demandas clássicas para as quais um produto criativo envolve, necessariamente, uma transformação radical da vida humana, segundo a ideia de níveis de criatividade; essa teoria deweyiana constitui um insight interessante para a promoção da atitude criativa; esse processo criativo preserva a mesma estrutura em todos os casos - ciência e arte, por exemplo - e essa criatividade é, agora, uma potencialidade intrínseca dos seres humanos - a qual pode ser realizada ou não. Por fim, consideramos a relevância de alguma tese deweyiana para as posições atuais, como no caso do psicólogo cognitivo Robert Weisberg, enfatizando as coincidências e desacordos de ambos.
Keywords: Creatividad; Innovación; Imaginación; John Dewey; Creativity; Imagination; Innovation; John Dewey